Trends in Level of Evidence of Systematic Reviews in Sports Medicine, 2010-2020 : A Systematic Review and Meta-analysis. Issue 9 (2nd September 2022) - Paras, Tyler; Sabzevari, Soheil; Solomon, David; Smith, Clair; McDonough, Christine; Lin, Albert
Background: Popularization of systematic reviews has been met with controversy because of concerns that the primary literature for certain topics may not be suited for systematic review and meta-analysis. Purpose: To assess the rate of publication of systematic reviews based on their level of evidence (LOE) in influential orthopaedic sports medicine journals and commonly studied topics in sports medicine. Study Design: Systematic review. Methods: An electronic search was performed using the PubMed database of studies published from January 2010 to December 2020. The advanced search function was used to identify systematic reviews from the Journal of Shoulder and Elbow Surgery ( JSES ), American Journal of Sports Medicine ( AJSM ), Arthroscopy, British Journal of Sports Medicine ( BJSM ), Journal of Bone and Joint Surgery–American Volume ( JBJS ), and Sports Medicine ( SM Auckland ), as well as reviews of the most common areas of sports medicine research, including rotator cuff repair (RCR), shoulder instability (SI), anterior cruciate ligament reconstruction (ACLR), and meniscal repair. The LOE was assigned to each included study according to the Oxford Centre for Evidence-Based Medicine. Studies were grouped as LOE 1-2, LOE 3-5, and nonclinical systematic reviews. A negative binomial regression was used to determine the changes in publication rate over time. Results: A total of 2162 systematic reviews were included in this study. From 2010 to 2020, the rate of publication of LOE 3-5 systematic reviews increased significantly among most of the surveyed journals ( AJSM, P < .0001; Arthroscopy, P = .01; BJSM, P < .0001; JSES, P < .0001; SM Auckland, P < .0001), with the exception of JBJS ( P = .57). The rate of publication of LOE 1-2 systematic reviews increased in AJSM ( P < .0001), Arthroscopy ( P = .02), BJSM ( P < .0001), and SM Auckland ( P < .0001); however, no significant changes were seen in JBJS ( P = .08) or JSES ( P = .15). The publication rate of LOE 3-5 systematic reviews increased for all sports medicine topics surveyed (meniscal repair, P < .0001; RCR, P < .0001; SI, P < .0001; ACLR, P < .0001). However, the publication rate of LOE 1-2 studies only increased for RCR ( P = .0003) and ACLR ( P < .0001). Conclusion: The rate of publication of LOE 3-5 systematic reviews exponentially increased in orthopaedic sports medicine journals over the past decade, outpacing the publication rate of LOE 1-2 systematic reviews.